The effect of benzyladenine on shoot regeneration in vitro of Zantedeschia aethiopica ‘Green Goddess’ - DANUTA KOZAK; MAGDALENA STELMASZCZUK (Annales Horticulturae, 2015)
Shoots of Zantedeschia aethiopica ‘Green Goddess’ obtained from aseptically grown shoot clusters were cultured in vitro on a Murashige and Skoog [1962] medium containing BA (benzyladenine) in concentrations: 5, 10, 25 and 50 μM. The control was a medium without of cytokinin. The highest number of axillary shoots was found on media with BA at concentration of 25 and 50 μM. The treatment with BA 25 μM stimulated the most formation of rhizomes. The roots occurred on the all of studied media. The best rooting was on the media with 5 or 10 μM of BA.